Permeability evolution across carbonate hosted normal fault zones. (April 2016) - Haines, Thomas J.; Michie, Emma A.H.; Neilson, Joyce E.; Healy, David
Abstract: Carbonate lithologies tend to have highly heterogeneous and tortuous pore systems that are created and/or modified by diagenetic and tectonic processes following deposition. The correlation between porosity and permeability in carbonate lithologies is often poor as a result of their heterogeneous and complex pore systems. To effectively predict permeability, it is necessary to understand the processes that modify pore systems and quantify the impact of these modifications on permeability. Using outcrop exposures of normal fault zones hosted in carbonate lithologies on the Maltese Islands, this study documents the evolution of textures in contrasting carbonate lithofacies (wackestones, packstones and pack/grainstones) across two normal fault zones of varying displacement ( c . 10 and 100 m). The pore system modifications associated with these textural changes are quantified using image analysis and point count methods, while porosity and permeability are measured across the studied fault zones using core plug porosimetry and permeametry techniques. The fault related processes that occur within the fault zones are controlled by the primary lithofacies and to a lesser extent the fault displacement. Aggrading neomorphism is observed within the damage zones in the grain supported lithofacies and is postdated by fracturing. In the micrite supported lithofacies in the same damage zones, aggrading neomorphism is absent, but fracturing is prevalent. In the fault core, brecciation occurs in both lithofacies within the 10 and 100 m displacement fault zones, while cataclasis is only active in the grain supported lithofacies in the higher displacement fault zone. The mineralogical and textural compositions of the primary lithofacies dictate the processes that occur in the fault zones. These processes variably modify the pore systems and hence control the temporal evolution of permeability in the fault zones. Such observations can help understand reservoir quality distribution around fault zones in the subsurface reservoirs. Highlights: Two categories of fault processes are active in carbonate hosted fault zones. Porosity occlusion processes, e.g. aggrading neomorphism, reduce permeability. Porosity creation processes, e.g. fracturing and dissolution, enhance permeability. The processes active are dependent on the lithofacies and the fault displacement. These processes control the spatial and temporal evolution of permeability.